Chapter L. Tolstoj lettore di scrittori e filosofi occidentali: fra indipendenza e appropriazione - Delaunay, Claire (Firenze University Press, 2022)
This article focuses on Tolstoy’s attitude towards the European writers he reads. From what he says about them (in his Diary, notes, letters, prefaces), we can characterize his attitude towards the Western cultural tradition in terms of independence and appropriation, and understand what conception of literature and philosophy emerges from his criteria of appreciation. It seems that Tolstoy places himself as a judge and as a mediator, through whom western writers must arrive to Russian readers, and that sincerity appears to be the most significant criterium in his conception.